A Fruitful Framework: Commentary for a More Integrative Approach. Issue 1 (23rd March 2017) - Klein, Juliana M.; Briggs, Erick P.
Abstract : Compared with more turbulent times in history, some might argue workplace discrimination has seen a downward trend. Others would contend that workplace discrimination has "just gone underground" and become more covert (Herring, 2002, p. 13). Either way, not-so-distant historical events such as the landmark Texaco case in 1996 and the Ford Motor case in 2000 remind us that discrimination demands our attention. Calls for research on interventions have surfaced (Becker, Zawadzki, & Shields, 2014 ), and proposals such as legal reforms, implicit bias training (Bartlett, 2009 ), and experiential learning workshops have answered (Cundiff, Zawadzki, Danube, & Shields, 2014 ). The focal article (Jones, Arena, Nittrouer, Alonso, & Lindsey, 2017 ) contributes to this discussion as it turns our attention to the construct space of discrimination and presents a framework for organizing its facets and forms. Without a doubt, a framework that lends itself to the integration of the many forms of discrimination is long overdue.